Extended Restorative Spaces - Al Dabbagh, Shamael Mohamed; Al Shahiry, Hind SafaaAldeen (Iraqi Journal of Architecture and Planning, 2018)
Stress and tension are considered among the most important characteristics of today’s modern society, which in turn affect the mental and physical health of the people, it affects negatively mostly on the ability of the person to focus and perform a mentally stressed tasks. in addition to the physical effects such as fatigue and exhaustion, and as a consequence it shows a falter in blood pressure levels, cholesterol and so on. Within such environment, the role of the architect and interior designer becomes more interesting to invest in social spaces and spaces of hospitality as a daily escape to temporary achieve rest and renewal of the human capabilities in ongoing efforts to meet adaptive demands of life. This research problem identified the lack of knowledge associated with the characteristics and designing elements for the interior restorative environments and supporting the concept of extending within the hospitality spaces (restaurants as a case study), where the research sought to encourage investing in restaurant spaces as a restorative spaces because it incorporating a wide range of types starting from luxury restaurants to fast food restaurants that are affordable to all social classes. In order to solve the research problem, the research adopted a hypothesis that states: â€œThe designing elements of restaurant space support and achieve extend characteristics and thus contribute to achieve restoration and reduce tension levelsâ€. The research focused on two main concepts in achieving the Extend, combining the physical extend (the concept of prospect) and conceptual extend which it consist of sub-concept that included (spirituality, characterization, and refuge).The research results proofed the main role of internal elements of restaurant spaces in achieving restoration relating to the concept of Extend .Finally the research ended displaying some of the conclusions and recommendations.